1979
DOI: 10.1007/bf00498757
|View full text |Cite
|
Sign up to set email alerts
|

Histamine receptors in the guinea pig ileum

Abstract: Histamine and some related compounds acting selectively on H2-or H1 receptors were tested for their ability to contract the guinea pig ileum, in the usual whole ileum preparation and in the longitudinal muscle preparation. The concentrations elicited by histamine in both kinds of preparations were not potentiated by cimetidine or metiamide and were not inhibited by administration of H2 receptor selective agonists in doses which were subthreshold for contracting the guinea pig ileum; higher doses of the H2 agon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1981
1981
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Histidine is converted to histamine by a specific enzyme, histidine decarboxylase. Histamine is known to contract several types of smooth muscle, including those of the bronchi, gut and large blood vessels [26] . Histamine-induced contraction of the smooth muscle of guinea pig ileum is mediated by H 1 receptors found throughout the gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 99%
“…Histidine is converted to histamine by a specific enzyme, histidine decarboxylase. Histamine is known to contract several types of smooth muscle, including those of the bronchi, gut and large blood vessels [26] . Histamine-induced contraction of the smooth muscle of guinea pig ileum is mediated by H 1 receptors found throughout the gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 99%
“…4). It has been reported that H2 receptors can be demonstrated in the ileal strip preparation (Ambache & Aboo Zar, 1970;Ambache, Killick & Aboo Zar, 1973;Bertaccini, Molina, Zappia & Zseli, 1979) and it was possible that activation of these was inhibiting 42K efflux in response to H1 activation. However, cimetidine (10-7-10-5 M), an H2 receptor blocker (Brimblecombe, Duncan, Durant, Emmett, Ganellin & Parsons, 1975) also did not increase…”
Section: Histaminementioning
confidence: 97%
“…For studies of a,-adrenoceptors, rabbit aortae (New7 Zealand White, Hazleton, Inc., Kalamazoo, MI) were employed, essentially as previously described [Hancock et al, 1995al. Antagonism of liistaminergic H, and niiiscarinic M, receptors in the isolated guinea pig ileurn (male, alhino Hartley, Charles Kiver, Inc., Portage, MI) against the contractile effects of histamine or carbachol, respec-tively, were performed as described [Bertaccini et al, 1979;arid Malta et al, 1982, respectively]. Data for antagonism expcrimcrits in isolated tissues were analyzed as clescribed [Schild, 19471. The effects of A-80426 or1 presyriaptic azadrcrioceptors controlling neurotransmitter release were further evaluated in rat atria (aZL3) arid rabbit pulmonary artery (azA) as described [ Connaughton and Docherty, 1990;and Endo et al, 1977, respectivcly].…”
Section: Isolated Tissue Bioassays For Functional Activity In Vitromentioning
confidence: 99%